VULVAR CANCER: CLINICAL AND ONCOLOGICAL MANAGEMENT STRATEGIES (International Seven Journal of Multidisciplinary, 2025)
Vulvar cancer is a gynecological neoplasm with low incidence, yet with significant clinical impact due to its frequently late diagnosis and the morbidity associated with treatment. In recent decades, a shift in its epidemiological profile has been observed, with an increase in cases among younger women, especially related to persistent infection with human papillomavirus (HPV) (OLAWAIYE; CUELLO; ROGERS, 2021; NOGUEIRA-RODRIGUES et al., 2025). Squamous cell carcinoma is the predominant histological subtype and develops through two etiopathogenic pathways: an HPV-dependent pathway, associated with high-grade vulvar intraepithelial neoplasia and a better prognosis, and an HPV-independent pathway, related to lichen sclerosus and differentiated vulvar intraepithelial neoplasia, which is more aggressive (SANCHEZ; RAFFI; KRAUS, 2022). Staging and inguinofemoral lymph node status are key prognostic determinants, reinforcing the importance of early diagnosis (PLANCHAMP et al., 2023). Treatment has evolved toward more conservative and individualized approaches, aiming to reduce morbidity without compromising oncological control (OLAWAIYE; CUELLO; ROGERS, 2021; JHINGRAN, 2022).